MEDIA MASSA DAN MASYARAKAT - Hamdani Thaha (IAIN Palopo, 2009)
The present of mass media in society generate various impact, both for negative and also positive. Expected by negative impact of media like penetration of Western civilization values, can be reduce various value and cultural from outside with abilityy society itself to become the net for a cultural resilience and local wisdom. Expected also for jurnalist to be presentation order through mass media pay attention to the code of etik and religion values so that can lessen the negative impact from media.